Dilepton Emission at Temperature Dependent Baryonic Quark-Gluon Plasma - Singh, Shougaijam Somorendro; Kumar, Yogesh (New Insights into Physical Science Vol. 12, 2021)
Dilepton emission is calculated from quark-gluon plasma (QGP) with the consideration of temperature dependent chemical potential (TDCP). The model is considered to be quasi-model and hence take the dynamical quark mass as a finite value dependence on temperature. The temperature in quark mass enhances in the growth of dilepton emission rates. The emission rate of dilepton spectrum is shown in the intermediate mass region (IMR) of 1.0 - 4.0 GeV and its rate is observed to be a strong increasing function of the temperature dependent chemical potential for quark and anti-quark annihilation.